RAMAN SPECTROSCOPIC STUDY OF H2O IN BIKITAITE: "ONE-DIMENSIONAL ICE" - Kolesov B.A.; Geiger C.A. (My University, 2002)
The zeolite bikitaite, Li2[Al2Si4O12]·2H2O, has structural channels containing infinite chains of H2O molecules running parallel to [010]. One hydrogen atom of an H2O molecule is weakly hydrogen bonded to an O atom of a neighboring molecule, while the other hydrogen atom is unbonded. The molecules are ordered and the chains they form have been called “one-dimensional ice.” Polarized Raman spectra of single crystals in the wavenumber range 40–4000 cm−1 were measured from 5 to 625 K. At low temperatures, four different O-H stretching vibrations can be observed between 3330 and 3600 cm−1, as well as H2O bending vibrations at about 1640–1650 cm−1. The two lower wavenumber hydrogen-bonded O-H stretching modes increase in wavenumber with increasing temperature, while the higher wavenumber non-hydrogen-bonded OH modes decrease in wavenumber. The temperature dependence of the linewidths of the O-H stretching modes and the degree of hydrogen bonding between neighboring H2O molecules show that the main cause of line broadening is modulation of the OH potential from low-energy thermal O···O vibrations in the H2O chains. At elevated temperatures, the different O-H stretching modes become similar in energy and only a single symmetric H2O stretching band is observed above 520 K. At these temperatures the H2O molecules lose their hydrogen bonding and are only bonded to Li cations at the walls of the channels.